Identification and functional analysis of a splice variant of mouse sodium-dependent phosphate transporter Npt2c - Nomura, Kengo; Ohi, Akiko; Tatsumi, Sawako; Honda, Naoko; Segawa, Hiroko; Hanabusa, Etsuyo; Kido, Shinsuke; Yamanaka, Setsuko; Ito, Mikiko; Kuwahara, Shoji; Onitsuka, Akemi; Aranami, Fumito; et al. (The Journal of Medical Investigation, 2012)
Mutations in the SLC34A3 gene, a sodium-dependent inorganic phosphate (Pi) cotransporter, also referred to as NaPi IIc, causes hereditary hypophosphatemic rickets with hypercalciuria (HHRH), an autosomal recessive disorder. In human and rodent, NaPi IIc is mainly localized in the apical membrane of renal proximal tubular cells. In this study, we identified mouse NaPi IIc variant (Npt2c-v1) that lacks the part of the exon 3 sequence that includes the assumed translation initiation site of Npt2c. Microinjection of mouse Npt2c-v1 cRNA into Xenopus oocytes demonstrated that Npt2c-v1 showed sodium-dependent Pi cotransport activity. The characterization of pH dependency showed activation at extracellular alkaline-pH. Furthermore, Npt2c-v1 mediated Pi transport activity was significantly higher at any pH value than those of Npt2c. In an in vitro study, the localization of the Npt2c-v1 protein was detected in the apical membrane in opossum kidney cells. The expression of Npt2c-v1 mRNA was detected in the heart, spleen, testis, uterus, placenta, femur, cerebellum, hippocampus, diencephalon and brain stem of mouse. Using mouse bone primary cultured cells, we showed the expression of Npt2c-v1 mRNA. In addition, the Npt2c protein was detected in the spermatozoa head. Thus, Npt2c-v1 was expressed in extra-renal tissues such as epididymal spermatozoa and may function as a sodium-dependent phosphate transporter. J. Med. Invest. 59: 116-126, February, 2012